Psychological Distress, Uncertainty Intolerance, and Quality of Life of Patients with Cancer and Their Caregivers: A Comparative Study - Rahma, Ainur; Effendy, Christantie; Lismidiati, Wiwin (http://dharmais.co.id/, 2025)
Background: Psychological distress and uncertainty intolerance in cancer patients are linked to various physical consequences and negative psychological impacts, such as increased symptom severity, disruption in daily life, and reduced quality of life. These issues also affect family caregivers of cancer patients. This study aims to describe the psychological distress, uncertainty intolerance, and quality of life in cancer patients and their family caregivers. Methods: This was a cross-sectional study with 57 cancer patients and 57 caregivers at Dr. Sardjito Hospital, Yogyakarta-Indonesia, in July-August 2023. Psychological distress was measured by using the Kessler Scale (K-10), uncertainty using the Intolerance Uncertainty Scale (IUS-12), and quality of life using the EORTC QLQ-C30 and SF-36. Data were analyzed using Mann-Whitney and Kruskal-Wallis tests. Results: Significant differences were found in uncertainty intolerance between patients and caregivers (p=0.001) and caregivers’ marital status (p=0.045). Quality of life varied among patients based on age, gender, marital status, cancer type, and treatment (p0.05). Caregivers’ quality of life differed by age in physical and emotional roles (p≤0.005). Conclusions: There is a significant difference between the intolerance uncertainty of cancer patients and family caregivers. Meanwhile, the quality of life of cancer patients and the quality of life of family caregivers have differences in each scale and domain in several of their demographic characteristics. Longitudinal studies are needed to understand the trajectory of psychological distress and uncertainty intolerance over time.